1999
DOI: 10.1080/00102209908924185
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Analysis of Gaseous Fuel and Air Mixing

Abstract: Results are presented from a new mathematical model on the mixing of fuel and air. The model is derived from the ideal gas law and the equation of continuity. The equivalence ratio measured within an infinitesimal fluid element of mixture and the time rate of the equivalence ratio are used to quantify the degree and time rate of mixing. The model shows that in addition to the fuel molecular weight, the mixing rate depends on pressure, temperature, density, and their rates. The density rate depends on velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…(18). These results are in agreement with previous studies, 15 which showed that the rate of mixing is enhanced by reducing the initial pressure or increasing the rate of pressure.…”
Section: Resultssupporting
confidence: 95%
See 4 more Smart Citations
“…(18). These results are in agreement with previous studies, 15 which showed that the rate of mixing is enhanced by reducing the initial pressure or increasing the rate of pressure.…”
Section: Resultssupporting
confidence: 95%
“…These results are in agreement with previous studies 15 that showed a reduction in the rate of mixing at high temperatures and increase in the rate of mixing at high rates of temperature. 15 Rates of temperature of less than 1,000 K/s provide mixing times in excess of 0.3 s. Figure 6 shows the affect of temperature on maximum fuel-lean mixing time. A constant density of 1.2 kg/m 3 and two initial temperatures of 293 and 1465 K, respectively, are considered here.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations